Multiplication Gain and Excess Noise Factor in Double Heterojunction Avalanche Photodiodes - A. H., You; S. L., Tan; T. L., Lim; P. L., Cheang (2008)
A three layers double heterojunction avalanche photodiode (DHAPD) model is developed using Monte Carlo (MC) method to study the multiplication gain and excess noise factor. It is based on the statistical approach to determine the mean multiplication and excess noise factor due to the impact ionization of electron and hole travels in the high electric field. Our model is able to take into the consideration of the higher order impact ionizations that iterate from the second and third layers to represent the real multiplication processes in the DHAPD. The avalanche characteristics in DHAPD are possibly obtained by incorporating the deadspace effect, d(ij), hole to electron coefficients ratio, k(i) and heterointerface probability, p(ij). The dead-space effect is known in reducing noise in homojunction and single heterojunction APDs in our previous models. The probability of electron and hole to cross the heterointerface is another factor which eliminates the secondary impact ionizations in the device. However, these effects are not shown in this work for simplicity. Instead of that we are interested to demonstrate the effect of hole to electron coefficients ratio where the number of hole feedback impact ionizations is the dominant effect to improve the excess noise factor in DHAPD. It is shown that the parameters (such as k(i) ratio, electron and hole ionization coefficients) in the second layer of DHAPD are importantly controlling the characteristics of the device.